Eduard Petru's legacy in the study of medieval literature with regard to Petr of Chelcice's work - Soleiman Pour Hashemi, Michaela (Bohemica Olomucensia, 2019)
The study deals with the contribution of the Olomouc professor Eduard Petru (1928-2006), especially to the research on the work of Petr of Chelcice and his personality (ten basic studies and two editions in total). First, the author presents substantial publications in which E. Petru dealt with the topic. She concludes that the most frequently cited item is his List of Chelcicky's Works. Furthermore, she summarizes that the legacy of E. Petru in Chelcicky's research is followed in particular by Jaroslav Boubin (1954), who is still the author of six publications connected with Chelcicky (2005-2018), in which E. Petru is also properly cited. In a note, she states that in the line of E. Petru she translated Chelcicky's texts into new Czech (together with Jan Rokyta) in the publication The Time and Work of Petr Chelcicky (2013). Finally, she concludes that the research legacy of E. Petru is alive, also thanks to the university textbooks often used (Lehar et al. 1998; Machala et al. 2015).
Keywords: Eduard Petru; Petr Chelcicky